Conocimiento e inserción de la responsabilidad social empresarial en las PyMES de la ciudad de Loja período 2013 - 2014 - Veintimilla Carrión, María Augusta (2014)
SMEs in Ecuador and in our province are the main engine in the socio-economic development which generate jobs this being their essential role, through optimizing the impacts of processes and products. The companies' CSR has become a tool that contributes to the competitiveness and above all, to the common good. This research's main objective was to determine the knowledge and integration of corporate CSR in SMEs city of Loja period 2013 - 2014, through two surveys of managers and workers, which allowed us to determine in a general way as is CSR in SMEs of Loja. And with the achievement of these results allowed a situation assessment, make proposals and recommendations to serve as tools for the actions of SMEs more effective and efficient and offer products and services of quality and warmth, that their actions have a immense commitment to the community and be more friendly to the environment. Keywords: